ANALISIS PENERAPAN CATATAN ATAS LAPORAN KEUANGAN UNTUK LAPORAN REALISASI ANGGARAN BERDASARKAN PSAP NO 04 PADA DINAS KEHUTANAN KABUPATEN KETAPANG - B51111053, Bramantyo Widi Nugroho (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This purpose of the study to determine whether the Forest Service has implemented the Ketapang District Government Accounting Standard ( PSAP ) No. 04 of the Notes to the Financial Statements and what factors cause the already / not yet suitability of application of Notes to Financial Statements for the Budget Realization Report conducted Ketapang Forestry Service. To analyze the application of the Notes to the Financial Statements for the Budget Realization Report by PSAP No. 04 in Ketapang District Forestry Office , the writers conducted interviews , documentary studies , and literature study to find out how the application of the Notes to the Financial Statements for the Budget Realization Report by PSAP No. 04 and what factors are causing already / not yet suitability PSAP application No. 04 .                The analysis shows that in the preparation and presentation of financial statements Ketapang District Forestry Office as a whole is still not fully in accordance with Government Accounting Standard (PSAP) No. 04 of the Notes to the Financial Statements which have never presents obstacles and constraints encountered in the achievement of performance targets, not to disclose information required by Statement of Governmental Accounting Standards that is not presented in the cover sheet financial statements and the absence of additional information necessary for fair presentation is not presented the cover sheet financial statements. Factors that cause is not incompatibility PSAP application No. 04 that the finance officer not contain financial statements educational background in accounting and lack of socialization regarding PSAP No. 04 by the related parties. Keywords : Notes to the Financial Statements, PP 71 in 2010, and PSAP No. 04